Teori-Teori Adaptasi Antar Budaya - Lusia Savitri Setyo Utami (Jurnal Komunikasi, 2015)
AbstractThis paper is a literature review of the theories of Intercultural Adaptation. The theory was included in the study Intercultural Communication (KAB). Adaptation is a problem that needs to be solved when a person or group of people communicate with others from different cultures. Cross-cultural adaptation process is an interactive process that evolves through communication activities between individual entrants with new socio-cultural environment. This paper uses a qualitative approach with descriptive analysis method. Through a case study, this paper presents how the theories of inter-cultural adaptations are implemented in the pattern of intercultural communication in everyday life when someone does adaptation, especially with a different culture from them. In this paper described five inter-cultural adaptation theory, namely Integrative Communication Theory, Anxiety / Uncertainty Management Theory, Uncertainty Reduction Theory, Theory of Acculturation and Culture Shock, and Co-cultural Theory. Theories of Intercultural Adaptation explains that adaptation is a collaboration of migrants effort and local environmental acceptance. Achieving maximum intercultural adaptation is when each individual entrants and individual local culture accept their culture of each other.AbstrakTulisan ini merupakan sebuah literature review  mengenai teori-teori Adaptasi Antar Budaya. Teori ini termasuk di dalam kajian Komunikasi Antar Budaya (KAB). Adaptasi merupakan suatu problema yang perlu dipecahkan ketika seseorang ataupun sekelompok orang berkomunikasi dengan pihak lain yang berbeda budaya. Proses adaptasi antar budaya merupakan proses interaktif yang berkembang melalui kegiatan komunikasi individu pendatang dengan lingkungan sosial budayanya yang baru. Tulisan ini menggunakan pendekatan kualitatif dengan metode analisis deskriptif. Melalui sebuah contoh kasus, tulisan ini menghadirkan bagaimana teori-teori adaptasi antar budaya tersebut diimplementasikan dalam pola komunikasi antar budaya sehari-hari ketika seseorang melakukan adaptasi, terutama dari sebuah budaya yang berbeda darinya. Di dalam tulisan ini dideskripsikan lima buah teori adaptasi antar budaya, yaitu Integrative Communication Theory, Anxiety/Uncertainty Management Theory, Uncertainty Reduction Theory, Teori Akulturasi dan Culture Shock, dan Co-cultural Theory. Teori-teori Adaptasi Antar Budaya tersebut menjelaskan bahwa adaptasi merupakan kolaborasi dari usaha pendatang dan penerimaan lingkungan setempat. Tercapainya adaptasi antar budaya yang maksimal adalah ketika masing-masing individu pendatang dan individu budaya setempat saling menerima budaya mereka satu sama lain.